Three new species of Capitellidae (Annelida) from France - Magalhães, Wagner F.; Lavesque, Nicolas; Lamarque, Bastien (Zootaxa, 2024)
Sampling in shallow sediments of Bay of Biscay up to 70 m has yielded three undescribed capitellids. Mediomastus biscayensis sp. nov. is distinct from its congeners by a combination of characters that includes the presence of bilimbate thoracic capillaries, thoracic and abdominal hooks similar in shape and length and distinct Methyl Green staining pattern with chaetigers 5–9 having sparse green speckles and chaetigers 10–11 with dense green speckles. Notomastus hutchingsae sp. nov. is a very distinct Notomastus species because of the presence of two achaetous segments in the thoracic region and the shape of the thoracic segments with a constriction after segment 4, and after segment 6 segments becoming distinctly separated and bi-annulated. The newly proposed Peresiella ellae sp. nov. is most similar to its Atlantic congener P. spathulata Ewing, 1984 by the absence of eyespots and presence of modified spatulate chaetae on chaetiger 4–11, but differing by the presence of two peristomial annuli, shape of thoracic and abdominal segments, number of spatulate chaetae per tori and dentition of hooded hooks. All species are fully described, illustrated and commented on according to their closest congeners.